Prevalence of airflow obstruction and reduced forced vital capacity in an Aboriginal Australian population: The cross‐sectional BOLD study. Issue 5 (22nd February 2015) - Cooksley, Nathania A.J.B.; Atkinson, David; Marks, Guy B.; Toelle, Brett G.; Reeve, David; Johns, David P.; Abramson, Michael J.; Burton, Deborah L.; James, Alan L.; Wood‐Baker, Richard; Walters, E. Haydn; Buist, A. Sonia; et al.
Abstract Background and objective Mortality and hospital separation data suggest a higher burden of chronic obstructive pulmonary disease (COPD) in indigenous than non‐indigenous subpopulations of high‐income countries. This study sought to accurately measure the true prevalence of post‐bronchodilator airflow obstruction and forced vital capacity reduction in representative samples of Indigenous and non‐Indigenous Australians. Methods This study applies cross‐sectional population‐based survey of Aboriginal and non‐Indigenous residents of the Kimberley region of Western Australia aged 40 years or older, following the international Burden Of Lung Disease (BOLD) protocol. Quality‐controlled spirometry was conducted before and after bronchodilator. COPD was defined as Global initiative for chronic Obstructive Lung Disease (GOLD) Stage 2 and above (post‐bronchodilator forced expiratory volume in 1 s/forced vital capacity (FEV1/FVC) ratio <0.7 and FEV1 < 80% predicted). Results Complete data were available for 704 participants. The prevalence of COPD, adjusted for age, gender and body weight in Aboriginal participants (7.2%, 95% confidence interval (CI) 3.9 to 10.4) was similar to that seen in non‐Indigenous Kimberley participants (8.2%, 95% CI 5.7 to 10.7) and non‐Indigenous residents of the remainder of Australia (7.1%, 95% CI 6.1 to 8.0). The prevalence of low FVC (<80% predicted) was substantially higher in Aboriginal compared with non‐Indigenous participants (74.0%, 95% CI 69.1 to 78.8, vs 9.7%, 95% CI 7.1 to 12.4). Conclusions Low FVC, rather than airflow obstruction, characterizes the impact of chronic lung disease previously attributed to COPD in this population subject to significant social and economic disadvantage. Environmental risk factors other than smoking as well as developmental factors must be considered. These findings require further investigation and have implications for future prevention of chronic lung disease in similar populations.